2021
DOI: 10.1155/2021/6695957
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality of Sliced Pawpaw (Carica papaya) and Watermelon (Citrullus lanatus) Sold on Some Streets of Accra Metropolis, Ghana

Abstract: In most African countries, street vending of fruits is prevalent and the likelihood of predisposing consumers to microbial contamination is very high. This study aimed to determine various bacteria and risk factors that are associated with fruits sold by street vendors in Accra. Sliced watermelons and pawpaws were randomly purchased from selected suburbs in Greater Accra Region of Ghana. One gram (1 g) of each watermelon and pawpaw was homogenized in 9 ml of sterile peptone water, and 0.1 ml from each serial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Enterobacter aerogenes, Providential alcalifactiens, and Klebsiella oxytoca strains occurred on the surfaces of watermelons in direct contact with the soil in both organic and conventional fields. The Enterobacteriaceae strains isolated in this study were similar to those reported in a similar study [ 16 ], where Citrobacter sp. Klebsiella sp., Enterobacter sp.…”
Section: Resultssupporting
confidence: 89%
“…Enterobacter aerogenes, Providential alcalifactiens, and Klebsiella oxytoca strains occurred on the surfaces of watermelons in direct contact with the soil in both organic and conventional fields. The Enterobacteriaceae strains isolated in this study were similar to those reported in a similar study [ 16 ], where Citrobacter sp. Klebsiella sp., Enterobacter sp.…”
Section: Resultssupporting
confidence: 89%
“…Notably, the total coliform count exceeded the faecal coliform count, indicating that the primary source of contamination was soil rather than faecal matter. Tese fndings align with similar investigations conducted in various regions of Ghana, as well as other developing nations [25,28,29]. Te detection of E. coli, Salmonella spp., and Shigella spp.…”
Section: Total Coliform Faecal Coliform and Enterococci Counts Insupporting
confidence: 81%
“…Studies conducted in Accra and Kumasi in Ghana (Cornish et al, 1999;Drechsel et al, 2000;Mensah et al, 2001;Keraita et al, 2002) have confirmed that most horticultural produce are contaminated using fresh poultry manure and also with contaminated irrigation water with fecal coliforms that exceed the WHO recommended level of 1 × 103, 100 mL -1 for unrestricted irrigation. Handling, especially during harvesting, slicing and transportation where good sanitary standards (such as washing with potable water) are lacking also results in the contamination of produce (Olu-Taiwo et al, 2021).…”
Section: Microbiological Hazardsmentioning
confidence: 99%
“…Although the consumption of fruits and vegetables has many benefits, food safety is still of great concern owing to poor pre and postharvest handling. Such poor practices result in the contamination of produce with foodborne hazards, which when consumed result in an escalation of foodborne illness (Olu-Taiwo et al, 2021). According to an FAO/WHO report, out of the 1,400 microbial species responsible for contaminating food, 58% were identified as zoonotic which included Listeria monocytogenes, Salmonella, and Escherichia coli O157:H7.…”
Section: Introductionmentioning
confidence: 99%